SOSIALISASI DAN EDUKASI PENERAPAN PROTOKOL KESEHATAN BAGI ANAK-ANAK DI KELURAHAN SAMKAI PADA MASA PANDEMI COVID-19: Socialization And Education In Implementation Of Health Protocols For Children In The Samkai Village During The Covid-19 Pandemic - Sajriawati Sajriawati; Nurliah Nurliah; Gardis Andari (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Corona virus prevention is very important to do by using the socialization method. Socialization is providing information about how to prevent the Corona virus. Corona virus prevention can be done by practicing social distancing, implementing clean living and self-isolation to avoid transmission of the virus. Children are an important priority to be educated to have a healthy lifestyle. The service activities carried out aim to educate children on the coast of Binaloka, Samkai Village, to improve security independently in dealing with the Covid-19 pandemic. The high activity and interaction of the children around can already be balanced with the awareness of children in terms of strict self-care against Covid-19, for example washing hands properly and adopting a healthy and clean lifestyle. Through this activity it is hoped that children's potential to be exposed to Covid-19 can be reduced, because children have tried to take preventive measures. Based on the results of the service, there was an increase from pre test to post test, namely knowledge about the dangers of the corona virus from 56% to 80%. Knowledge of the correct use of masks from 70% to 100%, and knowledge of the importance of washing hands from 68% to 85%. Based on the increase in scores from pretest to posttest, it can be concluded that community service activities regarding health outreach and education for children in Samkai Village were successful.